Model Kepemimpinan Adaptif Kepala Sekolah Dalam Menghadapi Disrupsi Pendidikan Era Digital - Syahruzi, Muhammad; Ramli, Akhmad (Universitas Pakuan, 2025)
ADAPTIVE LEADERSHIP MODEL OF SCHOOL PRINCIPALS IN FACING EDUCATIONAL DISRUPTION IN THE DIGITAL ERAThe digital era has generated a profound wave of disruption that has reshaped multiple dimensions of human life, including the educational sector. The rapid advancement of information and communication technologies compels school principals to assume roles beyond administrative functions, positioning them as adaptive leaders who are visionary and responsive to the dynamics of digital transformation. This study seeks to elucidate the model of adaptive leadership among school principals in addressing the challenges of educational disruption in the digital age. Employing a qualitative approach through a comprehensive literature review, this research examines diverse academic sources—such as scholarly journals, articles, and books—to identify the principles, strategies, and practices underpinning adaptive leadership in educational institutions. The findings indicate that adaptive leadership emphasizes the principal’s capacity to flexibly navigate technological shifts, articulate a coherent digital vision, foster continuous professional development among teachers, enhance collaborative engagement across the school community, and leverage data-driven decision-making. Adaptive principals serve as agents of change who strategically integrate technology into school management and instructional practices through approaches such as blended learning, digitally oriented project-based learning, and the utilization of Open Educational Resources (OER). Furthermore, adaptive leadership necessitates the preservation of core educational values, including the incorporation of Islamic principles within faith-based school contexts. In conclusion, adaptive leadership constitutes a pivotal factor in enabling schools to successfully navigate educational disruption in the digital era. Principals who embody adaptive leadership are able to transform challenges into opportunities, sustain educational relevance, and cultivate an innovative, collaborative, and competitive school culture amidst the dynamics of global change.